Assessment of the IEQ in Two High Schools by Means of Monitoring, Surveys and Dynamic Simulation. (December 2015) - Pistore, Lorenza; Cappelletti, Francesca; Romagnoni, Piercarlo; Zonta, Antonio
Abstract: This work presents an assessment of schools' indoor environmental quality, based on investigations carried out in three Italian classrooms in Treviso, in the North-East of Italy. A first monitoring campaign was performed during the mid season (May-June), a second one during the heating period (January-February). At a first stage, the study was focused on two different approaches, an objective and a subjective one, in order to compare the objective responses with the occupants' subjective sensations. The first method consisted of physical observations and field measurements of thermal environmental parameters, used to calculate Fanger's comfort indices and to apply a comfort adaptive model. The subjective approach was managed by giving students and teachers a survey about their personal judgment concerning the level of comfort perceived. Finally, a simulation model has been built-up and calibrated using the indoor values of air temperature and air humidity trends collected by data loggers. A generic optimization program has been used to calibrate the thermal model. The responses from measurements, surveys and simulations were integrated, analyzed and compared, obtaining a good agreement between the three approaches in assessing the classroom thermal comfort category.